2022
DOI: 10.1088/2516-1091/ac4512
|View full text |Cite
|
Sign up to set email alerts
|

Wave-based optical coherence elastography: the 10-year perspective

Abstract: After ten years of progress and innovation, optical coherence elastography (OCE) based on the propagation of mechanical waves has become one of the major and, perhaps, one of the most studied OCE branches, producing a fundamental impact in the quantitative and nondestructive biomechanical characterization of tissues. Preceding previous progress made in ultrasound and magnetic resonance elastography; wave-based OCE has pushed to the limit the advance of three major pillars: (1) implementation of novel wave exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 194 publications
0
77
0
Order By: Relevance
“…The measurement of tissue biomechanics typically centers on Young’s modulus, a representation of elasticity expressed as the slope between the force (stress) and the resulting fractional deformation (strain). By analogy with ultrasound elastography, the most commonly used OCE method is based on the measurement of shear (or surface) elastic-wave propagation velocities for Young’s modulus estimation ( Doyle, 1997 ; Song et al, 2013a ; Wang and Larin, 2014 ; Zvietcovich and Larin, 2021 ). However, it has been frequently reported that the shear wave model is useful in bulk tissues/organs, such as the liver and kidney (using ultrasound- or MRI-based elastography detection), but would likely fail in tissues with thin layers and complex boundary conditions, such as the cornea and skin, hence the interest in developing alternative methods ( Pelivanov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of tissue biomechanics typically centers on Young’s modulus, a representation of elasticity expressed as the slope between the force (stress) and the resulting fractional deformation (strain). By analogy with ultrasound elastography, the most commonly used OCE method is based on the measurement of shear (or surface) elastic-wave propagation velocities for Young’s modulus estimation ( Doyle, 1997 ; Song et al, 2013a ; Wang and Larin, 2014 ; Zvietcovich and Larin, 2021 ). However, it has been frequently reported that the shear wave model is useful in bulk tissues/organs, such as the liver and kidney (using ultrasound- or MRI-based elastography detection), but would likely fail in tissues with thin layers and complex boundary conditions, such as the cornea and skin, hence the interest in developing alternative methods ( Pelivanov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transient tissue stimulation methods (e.g., impulse stimulation functions ( Wang et al, 2013 ) and square-wave modulation ( Crecea et al, 2009 )) can provide broadband stimulation frequencies simultaneously, thereby reducing acquisition time, safety, and comfort for patients. Conversely, wider temporal stimulus duration results in narrower frequency bandwidth responses ( Ramier et al, 2019 ; Zvietcovich and Larin, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal biomechanics in living tissues can be an indicator of pathologies or injury, and as such, the measurement and quantification of biomechanical properties of tissue is relevant to support early diagnosis of diseases 1 4 . A considerable amount of recent research effort has been focused on the development of measurement techniques for the quantification of biomechanics in ocular tissues, particularly in the cornea 1 , 3 , 5 15 although, in recent years, a number of techniques were adapted for the estimation of biomechanics in the crystalline lens (e.g. 16 18 ) and the sclera (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a number of techniques for the assessment of corneal tissue biomechanics such as, Ultrasound Elastography (USE) 31 , 32 , Magnetic Resonance Elastography (MRE) 33 , Brillouin microscopy 8 , 34 , air-puff deformation imaging 35 37 , and Optical Coherence Elastography (OCE) 1 , 3 5 , 34 . OCE, an optical technique which is applicable in vivo, is extensively used in corneal biomechanics research owing to its superior resolution, sensitivity and potentially non-contact nature 1 , 5 , 25 , 38 . OCE measures the mechanical response of tissues to external stimuli such as ultrasound excitation or air-puff on a multitude of spatial scales depending on application.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, OCE resolves the local displacement field in a sample subjected to external mechanical stimuli, such as quasi-static loads Wang et al (2006); Kling et al (2020). Dynamic OCE methods, with the measurement of shear-dominated stress wave generated from oscillatory or impulse stimuli Liang et al (2010); Zvietcovich and Larin (2022), reveal viscoelastic behavior of materials and has been demonstrated on biological tissues Han et al (2015); Kirby et al (2017); Ramier et al (2019) and environmental biofilms Liou et al (2019aLiou et al ( , 2021; Li et al (2020).…”
Section: Introductionmentioning
confidence: 99%